2009
DOI: 10.1002/macp.200800542
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent and Ionochromic Polyiminofluorene with Conjugated Terpyridine Substituent Groups

Abstract: Poly(N‐(4‐(2,2′:6,2″‐terpyridyl)phenyl)imino‐2,7‐fluorenylene P1‐2 was prepared upon palladium‐catalyzed polycondensation of 2,7‐dibromo‐9,9‐di‐n‐hexylfluorene 1 and 4′‐(4‐aminophenyl)‐2,2′:6,2″‐terpyridine 2 with 80% yield. MALDI–TOF spectroscopy indicated a maximum degree of polymerization of 14, the most abundant species being the pentamer and the hexamer. P1‐2 is highly fluorescent in solution. The emission maximum in chloroform is 510 nm, and the quantum yield Φf is 55%. UV/Vis titration of P1‐2 with zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…10,11 Hg 21 ions in the environment can be transformed into lipophilic organomercury derivatives (CH 3 HgX) and accumulates in the human body through the food chain. 13,15,[17][18][19][20][21][22][23] Dansyl fluorophore, which consists of dimethylamino moiety as a donor part and naphthalene sulfonyl as an acceptor part, has been widely used in fluorescence sensing applications due to its strong fluorescence in the visible region with high quantum yields. 1,13,14 The development of sensitive, robust, reliable, and portable analysis methods for the detection of metal ions has drawn a great deal of attention.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Hg 21 ions in the environment can be transformed into lipophilic organomercury derivatives (CH 3 HgX) and accumulates in the human body through the food chain. 13,15,[17][18][19][20][21][22][23] Dansyl fluorophore, which consists of dimethylamino moiety as a donor part and naphthalene sulfonyl as an acceptor part, has been widely used in fluorescence sensing applications due to its strong fluorescence in the visible region with high quantum yields. 1,13,14 The development of sensitive, robust, reliable, and portable analysis methods for the detection of metal ions has drawn a great deal of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dihedral angle (0.16°) between two neighboring pyridine rings with binding Zn 2+ was smaller than that without Zn 2+ (38.7°). These results indicate that the more highly planar and rigid terpyridineZn 2+ complex reduced the twist and vibration of the C-C polymer backbone and enhanced the charge transfer from donors to acceptors [41][42][43].…”
Section: Ion Sensing Propertiesmentioning
confidence: 87%
“…To adjust polarity and therefore solubility, as well as to enhance sensing characteristics, terpy motifs have been combined into a variety of organic, organometallic, and supramolecular architectures. These structures were applied for metal ion sensing [10][11][12], counter anion sensing [8,13,14], sensing of bio-molecules [15,16], and for bio-imaging [17]. Incorporation of terpy derivatives into polymeric matrices often results in the formation of functional materials that can be employed as effective sensors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of terpy derivatives into polymeric matrices often results in the formation of functional materials that can be employed as effective sensors [18]. For example, solutions of polyiminofluorene based polymer decorated with terpy groups were utilized as a highly sensitive and specific fluorimetric zinc sensor in organic solvent media [10]. Very recently, Garcia et al reported the incorporation of the terpy motif into water soluble acrylic polymers for colorimetric detection of Fe 3+ , Co 3+ , Sn 2+ , and Cu 2+ in solution and on solid film [19].…”
Section: Introductionmentioning
confidence: 99%